Multimodal imaging of hereditary retinal dystrophies (a series of clinical cases) - S. V. Milash; I. V. Zolnikova; V. V. Kadyshev (Российский офтальмологический журнал)
Multimodal visualization data of inherited retinal degeneration (IRD) on a Mirante platform (Nidek, Japan), used in a number of clinical cases, is compared with the data obtained by electrophysiological diagnostic methods. 4 patients with varying IRD were examined: adult-onset foveomacular vitelliform dystrophy, Stargardt disease, including those with fundus flavimaculatus, and retinitis pigmentosa. Multimodal imaging includes: colour fundus imaging, fundus autofluorescence, retro mode, and optical coherence tomography. Electroretinography was performed using an MBN electroretinograph (Russia), and electrooculography was performed using a RETIscan Science system (Roland Consult, Germany). Using non-invasive retinal imaging methods, specific patterns of inherited dystrophies were shown, which correlated well with the data of electrophysiological research methods. The combination of multimodal imaging on the Mirante platform (Nidek, Japan) in combination with electrophysiological diagnostic methods can be successfully used in complex diagnostics, monitoring of the progression, and evaluation of the results of IRD treatment.